The Effect of Make A Match Learning Model on Students’ Science Cognitive Competency of Junior High School Students In Payakumbuh City - Silvina Arifa; Ardi Ardi; Relsas Yogica; Ramadhan Sumarmin (ATRIUM PENDIDIKAN BIOLOGI, 2019)
This research is an experimental research which aims to see the effect of make a match learning model on students' knowledge competency in circulatory system material at SMPN 3 Payakumbuh academic year 2018/2019. The implementation of the study did not allow the researcher to control variabel as a whole so that this study belongs to the quasi experiment category with a randomized control group posttest only design. Sampling in this study using purposive sampling technique. Data analysis techniques using statistical tests namely t test. The results of the statistical test show that in a significant term (α = 0.05) obtained the value of tcount> t table, which is 3.32> 1.67 then H0 is rejected and H1 is accepted. It can be concluded that the knowledge competency of students by using the make a match learning model is higher than the knowledge competency of students who use conventional learning. It can be interpreted that there is the influence of the make a match learning model on students' knowledge competencies in circulatory system material at SMPN 3 Payakumbuh.